Primary Sjogren's syndrome and the risk of acute pancreatitis: a nationwide cohort study. Issue 8 (11th August 2017) - Chang, Chi-Ching; Chang, Yu-Sheng; Wang, Shu-Hung; Lin, Shyr-Yi; Chen, Yi-Hsuan; Chen, Jin Hua
Abstract : Objective: Studies on the risk of acute pancreatitis in patients with primary Sjogren's syndrome (pSS) are limited. We evaluated the effects of pSS on the risk of acute pancreatitis in a nationwide, population-based cohort in Taiwan. Study design: Population-based retrospective cohort study. Setting: We studied the claims data of the >97% Taiwan population from 2002 to 2012. Participants: We identified 9468 patients with pSS by using the catastrophic illness registry of the National Health Insurance Database in Taiwan. We also selected 37 872 controls that were randomly frequency matched by age (in 5 year bands), sex and index year from the general population. Primary outcome measure: We analysed the risk of acute pancreatitis by using Cox proportional hazards regression models including sex, age and comorbidities. Results: From 23.74 million people in the cohort, 9468 patients with pSS (87% women, mean age=55.6 years) and 37 872 controls were followed-up for 4.64 and 4.74 years, respectively. A total of 44 cases of acute pancreatitis were identified in the pSS cohort versus 105 cases in the non-pSS cohort. Multivariate Cox regression analysis indicated that the incidence rate of acute pancreatitis was significantly higher in the pSS cohort than in the non-pSS cohort (adjusted HR (aHR) 1.48, 95% CI 1.03 to 2.12). Cyclophosphamide use increased the risk of acute pancreatitis (aHR 5.27, 95% CI 1.16 to 23.86). By contrast, hydroxychloroquine reduced the risk of acute pancreatitis (aHR 0.23, 95% CI 0.09 to 0.55). Conclusion: This nationwide, retrospective cohort study demonstrated that the risk of acute pancreatitis was significantly higher in patients with pSS than in the general population.